The Relationship of Emotional Burnout and Personality Characteristics of Teachers - Soroka, Anatolii; Gmyr, Olga (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The article presents the results of an empirical study devoted to the study of the relationship between emotional burnout and personal characteristics of teachers. The subjects included 60 teachers of different age and work experience. It is proved that in the group of teachers with experience of 3-10 years high results were obtained on the scales of communicative speed and intellectual emotionality, and the group of teachers with experience of 11-30 years were found at a higher level of formation on the scales of resistance phase, emotional symptoms -moral disorientation, reduction of professional responsibilities, psychosomatic, psychovegetative disorders, intellectual ergism and control scale than in the group of teachers with 3-10 years of experience. The most pronounced component of the emotional burnout syndrome in the general sample is depersonalization, which is manifested in the deformation of interpersonal contacts with the environment in the form of increasing negativity towards them. A statistically significant positive correlation was found in the overall subjects between the variables of emotional burnout such as stress phase, emotional exhaustion, reduction of personal achievements with such variables of personality traits as communicative emotionality, indices of general emotionality and general activity. In other words, the higher the level of personality traits, the better teachers prevent the occurrence of emotional burnout. There were shown negative correlations in the general in subjects studied between such variables of emotional burnout syndrome as stress phase, symptom of traumatic circumstances, symptom of personal alienation, emotional exhaustion with such variables of personality traits as communicative ergicness and intellectual speed. Negative psychological manifestations of emotional burnout in teachers, such as increased irritability, decreased self-control which leads to professional destruction, deformation, crises, stress and other negative formations were found. The obtained results can be used in the practical work of a psychologist with teachers.